Hubungan Status Sosial Ekonomi dengan Indeks Massa Tubuh (IMT) di Kecamatan Tamalanrea Kota Makassar - Meilinda Aji Syahputri; Zulfahmidah Zulfahmidah; Windy Nurul Aisyah (Indonesian Journal of Health, 2021)
Background: Nutrition is a factor that plays an important role in the development of a nation. One simple waythat can be used to determine nutritional status is to measure the Body Mass Index (BMI) or Body Mass Index(BMI). One of the factors that play a role in determining a person's nutritional status is the socioeconomic level.The socio-economic level includes education, income, and work which are indirect causes of nutritionalproblems. Efforts to improve good health are related to economic capacity with income levels and socialconditions of household members. How economics plays a role in the health record of each individual. Thepurpose of this study was to see the status of the socio-economic relationship with the Body Mass Index (BMI).Methods: This study is a descriptive research design. Data collected using a questionnaire. The data of thisstudy were categorical variables from 2 groups so that it used the Chi-Square test. Results: From 84 samples,based on the calculation of IBM SPSS Statistic 23 using the Chi-Square analysis test, it was obtained that the P-value (0.125) ≥ 0.05, then H0 was accepted and Ha was rejected, meaning that there was no influence of BMIinfluence on socio-economic factors. Conclusion: There is no relationship between socioeconomic status andBody Mass Index (BMI).